Analisis “Pemecahan Masalah Matematis” Siswa Ditinjau dari Minat Belajar di SD” - Dina Anika Marhayani; Tandri Aisah; Evinna Cinda Hendriana (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
The background of this research is students' interest in learning and students' mathematical problem solving abilities are classified as low. This study aims to (1) describe students' interest in learning; (2) describe students' mathematical problem solving abilities and (3) describe students' mathematical problem solving abilities in terms of interest in learning. This research method is descriptive qualitative research. The results showed that, (1) students' interest in learning had an average of 72.78 high categories, (2) students' mathematical problem solving abilities had an average of 50.23 moderate categories, and (3) students' mathematical problem solving abilities. in terms of student learning interest, namely (a) students' mathematical problem solving abilities in terms of high learning interest are able to carry out all indicators according to Polya well and have an average of 62.70; (b) students' mathematical problem solving abilities in terms of interest in learning are being able to carry out understanding problems well, students simply plan problem solving and solve problems according to the plan and students are not good at re-checking their answers and have an average of 43.75; and (c) students' mathematical problem solving abilities in terms of low learning interest are able to carry out indicators of understanding problems quite well, planning solutions, solving problems according to plan and re-examining not well and has an average of 15.63